PENGARUH PUPUK ORGANIK DAN POC DARI KOTORAN KAMBING TERHADAP PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) - Muhammad Anshar, Yohanis Tambing, Sukmawati Suparhun (AGROTEKBIS, 2015)
The experiment was conducted to determine the composition of bokashi fertilizer and liquid organic fertilizer concentration of goat manure on the growth of mustard. This research has been conducted in the Binangga Village, Marawola Sub. District, Sigi Regency since August to November 2014. The research was arrangedbase on Randomized Block Design (RBD) consisting of three levels: control, bokashi 30 tons / ha, liquid organic fertilizer 5 cc / liter, bokashi 15 tons / ha + POC 5 cc / liter, bokashi 30 tons / ha + POC 2,5 cc / liter, bokashi 15 tons / ha + POC 2,5 cc / liter, bokashi 30 tons / ha + POC 5 cc / liter. Thus, there are 7 treatments was repeated 3 times. Data were analyzed by analysis of variance followed by Honestly Significant Different (HSD), if there is a treatment effect on the growth of mustard. The results showed that giving of bokashi organic fertilizer goat manure waste and waste liquid organic fertilizer manure goat very significant effect on the parameters of plant height, number of leaf, leaf area, fresh weight of crown and root, crown dry weight and root crops and fresh weight the total cropand dry weight the total crop. Bokashi organic fertilizer treatment and the best liquid organic fertilizer on growth is at a dose of 15-30 tonnes / ha + POC 2,5-5cc / liter.